2017
DOI: 10.3390/nu9040351
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Pregnancy Body Mass Index Is Associated with Dietary Inflammatory Index and C-Reactive Protein Concentrations during Pregnancy

Abstract: There have been a limited number of studies examining the association between pre-pregnancy body mass index (BMI) and dietary inflammation during pregnancy. Our aim is to examine the association between pre-pregnancy BMI and the Dietary Inflammatory Index (DII)™ and C-reactive protein (CRP) concentrations during pregnancy. The study included 631 pregnant American women from the National Health and Nutrition Examination Survey (NHANES) cross-sectional examinations from 2003 to 2012. Pre-pregnancy BMI was calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 54 publications
2
74
0
Order By: Relevance
“…Our findings are possibly explained by the knowledge that diet is a key modifiable determinant of inflammation. 18 For instance, the presence of trans fatty acids (i.e. in margarine) in the Western diet may increase systemic inflammation and endothelial dysfunction found in PAH, 31 whereas docosahexaenoic acid and eicosapentaenoic acid (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings are possibly explained by the knowledge that diet is a key modifiable determinant of inflammation. 18 For instance, the presence of trans fatty acids (i.e. in margarine) in the Western diet may increase systemic inflammation and endothelial dysfunction found in PAH, 31 whereas docosahexaenoic acid and eicosapentaenoic acid (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36][37][38] Another explanation for the lack of an association in the overweight/obese group could be because of the chronic inflammation and endothelial dysfunction that already exists in obesity. [18][19][20]39 It is possible that this underlying inflammation overpowers the effect of other determinants, such as diet. However, the underlying mechanism for the association between pre-pregnancy BMI and PAH remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shin et al . found that a high BMI prior to pregnancy is associated with a pro‐inflammatory diet and high levels of CRP during pregnancy .…”
Section: Discussionmentioning
confidence: 99%
“…Shin et al . found that a high BMI prior to pregnancy is associated with a pro‐inflammatory diet and high levels of CRP during pregnancy . In order to evaluate the inflammatory potential of diet in terms of the risk of recurrent miscarriage, Vahid et al .…”
Section: Discussionmentioning
confidence: 99%